Programmed cell death-associated gene transcripts in bovine embryos exposed to bovine Herpesvirus type 5 - Silva-Frade, Camila [UNESP]; Gameiro, Roberto [UNESP]; Okamura, Lucas Hidenori [UNESP]; Flores, Eduardo Furtado [UNESP]; Cardoso, Tereza Cristina [UNESP] (Elsevier B.V., 2014)
In vitro-produced bovine embryos become infected after exposure to bovine Herpesvirus type 5 (BoHV-5), yet no changes in developmental rates, mitochondrial activity and inhibition of apoptosis are detected in comparison to unexposed embryos. Thus, the aim of the present study was to assess the transcription of mitochondria-mediated apoptosis genes using TaqMan real-time polymerase chain reaction. Transcripts of mcl-1, caspase-2, -3, Apaf-1 and Bax genes were measured after exposure to BoHV-5 in vitro. Mitochondrial dehydrogenase activity was evaluated by MIT test and compared between groups of exposed and unexposed embryos, at day 7 of development. The rate of oocyte maturation was assessed by the extrusion of the first polar body. In summary, BoHV-5 exposed embryos retained their viability, mitochondrial dehydrogenase activity and displayed up-regulation of transcription of survival mcl-1 gene and down-regulation of Bax transcription in relation to mitochondria-mediated pathway which might improve embryo viability. These findings demonstrate that BoHV-5 exposed embryos maintain their viability and mitochondrial dehydrogenase activity with no compromise of embryos produced in vitro. (c) 2013 Elsevier Ltd. All rights reserved.
Keywords: Programmed cell death; Apoptosis; Alphaherpesvirus; Bovine embryos; Mitochondrion